Determinación de los riesgos biológicos que implican las actividades laborales del personal médico y de servicio del centro de salud tipo c del Cantón La Maná, aplicando la metodología biogaval como herramienta de valoración - Chigue Cunuhay, Mario David (2016)
In this study, 99 workers from the "La Mana" Health Center of a total of 137, who were considered exposed to biological agents, were selected: physicians, dentists, obstetricians, nurses, and laboratory personnel. The same ones that were evaluated by means of the "BIOGAVAL" method, is a practical procedure and is recommended to evaluate the biological risk in diverse work activities, in addition it allows to establish the level of biological risk and if it is the case to take corrective measures. For the application of this research, it was considered that the health workers who will be evaluated by this research method are also exposed to other types of risks due to workdays, schedules, overruns, etc., that when related to biological risk Increase the possibility of suffering any occupational disease or work accident. Because of the investigation we determined that the biological agents involved are hepatitis A virus, B virus, HIV virus, tuberculosis virus and influenza virus, it should be emphasized that hepatitis viruses are the least offensive Since it does not exceed the biological action level (NAB) = 12 nor the biological action limit (LAB) = 17. Based on the results obtained in the present study it is possible to recommend actions necessary to minimize the level of biological risk to which Each of the health workers in the present study is exposed. It can be determined that the adequate compliance of all hygienic measures established in the BIOGAVAL methodology results in a correction value of -3 and this reduces the risk level of each of the biological agents involved in the present study.